Integrative behavioral treatment for NREM parasomnias: a case series - Mundt, Jennifer M. (J Clin Sleep Med, 2021)
A variety of behavioral interventions have been shown to improve symptoms of non-rapid eye movement parasomnias. Prior reports have typically examined outcomes of a single behavioral intervention. However, non-rapid eye movement parasomnias may benefit from a multipronged treatment approach similar to that used in the behavioral treatment of other sleep disorders. Through a series of 3 case reports, we demonstrate the utility of a case-conceptualization based, integrative approach to behavioral treatment of adult non-rapid eye movement parasomnias. For all patients (2 with disorders of arousal and 1 with sleep-related eating disorder), symptoms were satisfactorily reduced after 3–6 sessions. Treatment was tailored to each individual, but common elements included education, hypnosis, and identifying and reducing priming factors (eg, stress, insufficient sleep) and precipitating factors (eg, noise or touch from bed partners). CITATION: Mundt JM, Baron KG. Integrative behavioral treatment for NREM parasomnias: a case series. J Clin Sleep Med. 2021;17(6):1313–1316.